Behavioral and Clinical Factors Associated with Self-Reported Abnormal Papanicolaou Tests in Rheumatoid Arthritis - Gillet, Victoria G (Mary Ann Liebert, Inc., 2014)
Background: Some evidence suggests that women with rheumatoid arthritis (RA) are at increased risk for the development of cervical cancer; however, it is unclear how this increase risk is conferred. We aimed to assess the factors related to abnormal Papanicolaou (Pap) tests in women with RA to determine whether they are similar to those reported for the general population. Methods: A structured questionnaire was mailed to 503 female patients from a longitudinal RA cohort. The survey included items on sociodemographic, behavioral, and gynecological factors. Univariate and multivariable logistic regression models examined the association of self-reported abnormal Pap results with a number of potential behavioral risk factors. Results: The questionnaire response rate was 57.5% (n=289). Median age was 61 years and 97% had ≥1 Pap test previously. Twenty-nine percent of respondents reported a previous abnormal Pap result. In the multivariable logistic model adjusted for age, number of lifetime sexual partners, age at menarche, birth control use, and history of sexually transmitted disease (STD), ever using birth control (odds ratio [OR] 2.31, 95% confidence interval [CI] 1.18–4.52) and previous STD (OR 3.38, 95% CI 1.70–6.70) were associated with an increased risk of abnormal Pap result. Compared with either the state or national population, a greater proportion of the respondents was older, married, and previous smokers, and completed postsecondary education and obtained a Pap test. Conclusions: In this cross-sectional study, self-reported abnormal Pap results were associated with use of birth control and history of STD in RA patients.